The Influence of Critical Thinking Implementation in Education: A Systematic Literature Review - Aska Daulika; Kasiyah Junus; Harry Budi Santoso; Jahns Michael; Ilma Alpha Mannix (Green Publisher Indonesia, 2025)
Critical thinking has emerged as a fundamental competency in 21st-century education, yet its effective implementation in educational settings remains challenging. While numerous pedagogical strategies exist to enhance critical thinking skills, there is limited comprehensive understanding of their impact on student engagement and the barriers to implementation across different educational contexts. This research aims to analyze the impact of critical thinking activities on student engagement and motivation. A systematic literature review was conducted following PRISMA guidelines, searching four databases (ScienceDirect, IEEE, Emerald Insight, Taylor & Francis) for publications from 2019-2024. The review employed a PICOC analysis framework and quality assessment criteria, ultimately analyzing 33 high-quality studies that met inclusion criteria. The analysis revealed that inquiry-based learning (IBL) and project-based learning (PBL) significantly enhance student engagement and motivation. Key barriers include inadequate teacher training (identified in 67% of studies), insufficient resources (45% of studies), and resistance to moving away from traditional teaching methods (52% of studies). Technology-enhanced pedagogical strategies, including collaborative learning platforms, game-based learning, and AI-assisted tools, demonstrated effectiveness in developing critical thinking skills. This research also highlights the importance of integrating technology in education as a means to support the development of critical thinking. These findings indicate that the development of critical thinking skills not only enhances student engagement but also prepares them to face real-world challenges.